Modern digital technologies in land management systems - Koshel, A.; Koshel, D. (Land Management, Cadastre and Land Monitoring, 2025)
Modern development of society is impossible without effective management of natural resources, among which land resources play a key role. Land is the basis of economic activity, a source of food security and an integral element of ecological balance. In this regard, there is a need to improve land management systems, especially in the context of the rapid development of digital technologies and the globalisation of information processes. The use of digital technologies, such as geographic information systems, remote sensing, big data and blockchain, creates new opportunities for effective monitoring, analysis and forecasting of land use changes. These tools help to ensure transparency of cadastral records, reduce the risks of abuse in land relations, and increase the accuracy and speed of management decision-making. At the same time, there is a growing demand for the integration of such technologies into management systems, which requires scientific justification and practical implementation. In the face of growing challenges related to urbanisation, climate change and land degradation, digital technologies are an important tool for supporting sustainable development. In Ukraine, where a significant portion of land resources is in a state of environmental hazard and management systems often remain outdated, the introduction of modern digital solutions is not only promising but also urgent. Thus, this article focuses on the current issues of integrating digital technologies into land management systems, which is essential for increasing their efficiency, transparency and sustainability. This study is aimed at identifying new approaches to solving land use problems adapted to modern challenges and needs of society. Key words: digital technologies, geographic information systems, remote sensing, land management, sustainable development.